Functional polymorphism of each of the two HLA-DR beta chain loci demonstrated with antigen-specific DR3- and DRw52-restricted T cell clones (The Rockefeller University Press, 1988)
HLA-DR3- and HLA-DRw52-associated functional polymorphism was investigated with selected tetanus toxoid (TT)-specific T cell clones. We have shown earlier that HLA-DR antigens are encoded by two distinct loci, DR beta I and DR beta III. The alloantigenic determinant(s) defined by the serological HLA-DR3 specificity map to the former, while the supratypic HLA-DRw52 determinants map to DR beta III. Furthermore, we have recently recognized by DNA sequencing three alleles of HLA- DRw52 at locus DR beta III, referred to as 52 a, b, and c. Our objective was to correlate the pattern of T cell restriction with the gene products of individual DR beta chain loci and with the three newly described alleles of locus DR beta III. Among the selected T cell clones, 5 reacted exclusively when TT was presented by HLA-DR3+ APCs (TT-DR3-APC). In contrast, two T cell clones were stimulated by TT- DRw52-APC. More specifically, these two T cell clones (Clones 10 and 16) were stimulated by different subsets of TT-DRw52-APC. Clone 16 responded to some DR3 and TT-DRw6-APC, while clone 10 was stimulated by other TT-DR3 and TT-DRw6, and all TT-DR5-APC. This same pattern of DRw52 restriction was found in panel, as well as in family studies. Because this suggested a correlation with the pattern of DRw52 polymorphism observed earlier by DNA sequencing and oligonucleotide hybridization, the APC used in these experiments were typed for the 52 a, b, and c alleles of locus DR beta III by allele-specific oligonucleotide probes. This distribution overlapped exactly with the stimulation pattern defined by the T cell clones. Clone 16 responded to TT-52a-APC, clone 10 to TT-52b-APC, and both clones to a TT-52c-APC. The response of the T cell clones was inhibited differentially by mAbs to DR. Raising TT concentration, or increasing HLA-class II expression with INF-gamma both affected the magnitude of response of the TT- specific clones but did not modify their specificities. These results demonstrate that a restriction specificity can be attributed to the DR beta III locus and illustrate the functional relevance of the polymorphism observed at this locus. This is of special interest in view of the striking difference in the pattern of structural diversity among alleles of DR beta I and DR beta III.